The stabilizing properties and energy indicators of electrical-ferromagnetic oscillatory circuit - A N Rasulov , G R Rafikova, M R Ruzinazarov (International Journal of Advanced Science and Technology, 2020)
This article outlines the stabilizing properties of electrical-ferromagnetic oscillatory circuit and defined stabilization effect of the dimensionless coefficients. It is proved that the falling part characteristics significantly depends on the linear inductance, considered energy indicators which are dependent on the electrical-ferromagnetic oscillatory circuit mode.